Deformation of the plasma concentration profile due field of the modulated electron beam: numerical simulation - Anisimov, I.O.; Kelnyk, O.I.; Siversky, T.V.; Soroka, C.V. (Вопросы атомной науки и техники, 2003)
Deformation of the concentration profile of the weakly inhomogeneous plasma due to the modulated electron beam was studied via computer simulation using big-particles-in-cells method. At the first stages the electric field increase in the local plasma resonance region was observed. It resulted to the density cavity formation. For the isothermic plasma the density cavity transformed into the plasma concentration jump. For plasma with the hot electrons ion-acoustic turbulence was observed at the late time points.